Single visit apexification technique by root end barrier formation with MTA (Update Dental College Journal, 2015)
Aim: To seal with Mineral trioxide aggragate(MTA) and make a sizeable communication between the root canal system and the periradicular tissue and provide a barrier because of lack of apical constriction.Summary: A 9 year old girl who had met with trauma about six years ago, before she visited department of Paediatric Dentistry , Update Dental College,Dhaka,Bangladesh for the treatment of mandibular right lateral incisor. The case was diagnosed as necrosis of pulp with open apex. After proper isolation access opening and biomechanical preparation was performed with 1mm short of the radiographic apex and calcium hydroxideused as intra canal medicament. After 15 days MTA was placed in the canal till a barrier of 4mm was achieved. Later obturation was done using lateral condensation technique.Size of the periapical lesion was almost decreased after one year of follow up. Followup was done after 1 month, 6 months and 1 year later.Update Dent. Coll. j: 2015; 5 (1): 21-25